(untitled) (Revista Cientifica Ingenio Magno, 2019)
Industrial wastewater requires control and management of its current production, according to existing literature, it is necessary that these are subjected to a quality treatment that works for continuous use and utilization, where it is also made an effective use of the water hyacinth floating macrofita (Eichhornia crassipes), which provides a treatment of industrial wastewater, obtaining high productivity and high efficiency of nutrient removal. This article aims to analyze the literature researched on macrophyte water hyacinth, involving, environmental sustainabili-ty, general aspects, background, design models, advantages and disadvantages, remediation, phytoremediation mechanism and current industrial wastewater treatment in the application of this phytoremediator method.